Comparison of anaesthetic efficacy of 4% articaine buccal infiltration versus 2% lidocaine inferior alveolar nerve block for pulpotomy in mandibular primary second molars - Seyedeh Hediyeh Daneshvar; Dariush Dorani; Mir Mahdi Daneshvar (Wolters Kluwer Medknow Publications, 2021)
Background: Pain control and proper anesthesia during pulp therapy is one of the most important aspects of behavior management in pediatric dentistry. Aims: This study compared the success rate of inferior alveolar nerve block (IANB) using 2% lidocaine and infiltration using 4% articaine for pulpotomy of mandibular primary second molars. Settings and Design: The present clinical trial was conducted on 40 children aged 5-8 referred to the Department of Pediatric Dentistry, Guilan University of Medical Sciences, who needed pulpotomy treatment in both mandibular second molars. The patients were randomly divided into two groups (A and B). Subjects and Methods: At the first session, Group A received articaine infiltration and Group B experienced IANB using lidocaine. At the next visit, this trend was reversed. Pain intensity was measured upon the initiation of the pulp exposure using a facial image scale (FIS) and the patients' behavior during pulpotomy was measured using sound eye motor (SEM). Statistical Analysis Used: Wilcoxon signed-rank test was used for the analysis of data. A significant level of differences was taken as P ≤ 0.05. Results: According to FIS, the pain upon the initiation of the pulp exposure was significantly lower in the lidocaine group (P = 0.028). Patients' behavior was also significantly better in the lidocaine group according to SEM (P = 0.028). Conclusions: IANB using lidocaine has higher anesthetic efficacy in the pulp therapy of the mandibular primary second molars compared to articaine infiltration.